2022
DOI: 10.1101/2022.03.18.484736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabinoids regulate an insula circuit controlling water intake

Abstract: The insular cortex, or insula, is a large brain region involved in the detection of thirst and the control of water intake. However our understanding of the topographical, circuit and molecular mechanisms the controlling water intake within the insula remains parcellated. We found that type-1 cannabinoid receptors (CB1) within the insular cortex participate to the regulation of water intake, and deconstructed circuit mechanisms of this control. Topographically, we revealed that the activity of excitatory neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…However, this is rarely the case when it comes to physiological hydration or satiety inputs and the aIC, that has is primarily involved in interoceptive processes in the context food poisoning or CTA ( Chen et al, 2020 ; Y. Wu et al, 2020 ). As other studies currently in press demonstrate, hydration correlates and requires decreased activity in aIC-BLA and increases in pIC-BLA CB1 receptor-expressing neurons ( Zhao et al, 2022 ). In fact, and in further accord with our previous findings ( Lavi et al, 2018 ; Kayyal et al, 2019 ), optogenetic activation of the aIC-BLA projection was found to be anxiogenic, while physiological conditions that are associated with negative valence and anxiety were encoded by changes in activity on the projection ( Nicolas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
“…However, this is rarely the case when it comes to physiological hydration or satiety inputs and the aIC, that has is primarily involved in interoceptive processes in the context food poisoning or CTA ( Chen et al, 2020 ; Y. Wu et al, 2020 ). As other studies currently in press demonstrate, hydration correlates and requires decreased activity in aIC-BLA and increases in pIC-BLA CB1 receptor-expressing neurons ( Zhao et al, 2022 ). In fact, and in further accord with our previous findings ( Lavi et al, 2018 ; Kayyal et al, 2019 ), optogenetic activation of the aIC-BLA projection was found to be anxiogenic, while physiological conditions that are associated with negative valence and anxiety were encoded by changes in activity on the projection ( Nicolas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
“…Subsequently, internal body state information reaches cortical regions through the thalamus. The insular cortex (or insula) and medial prefrontal cortex (mPFC) are reported as key interoceptive brain areas to sense internal body states and generate proper behaviors (Craig, 2003; Livneh and Andermann, 2021; Zhao et al, 2022; Zhao et al, 2020). In vivo imaging in the insula and electrophysiological recording in the mPFC showed specific feeding-response and drinking-response neurons (Eiselt et al, 2021; Livneh et al, 2017; Livneh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%